Synoeca‐MP: New insights into its mechanism of action by using NMR and molecular dynamics simulations approach. Issue 1 (30th July 2022) - Alves, Eliane Santana Fernandes; de Santos, Bruno de Paula Oliveira; Rodrigues, Leticia Valvassori; Freitas, Carlos Daniel Pereira; dos Santos, Lucianna Helene Silva; Dias, Simoni Campos; Franco, Octávio Luiz; Lião, Luciano Morais; de Magalhães, Mariana Torquato Quezado
Abstract: Synoeca‐MP is a 14‐residue amidated peptide, belongs to the mastoparan family and it is found in the venom of the wasp Synoeca surinama and has antibacterial and antifungal activity. The low cytotoxicity of the peptide also makes it an excellent candidate for drug development. To better understand its selectivity and interaction with the membrane, the peptide behavior in membrane‐like environments was studied here and the peptide structure in SDS micelles was determined by NMR spectroscopy. The behavior of the peptide in hydrophobic media and in different pH ranges was studied by CD spectroscopy. The incorporation of residues into the anionic micelles was studied by hydrogen‐deuterium exchange. The peptide stability and insertion in the micelles was studied by molecular dynamics simulations. Synoeca‐MP, bound to SDS micelles, exhibits a partial α‐helix conformation, with the first five residues and the last two unfolded. H/D exchange showed that the peptide has a slow exchange rate. After 164 h, four residues had not yet completed H/D substitution, suggesting parallel alignment of the peptide with the micelle, mainly due to the hydrophobic interface. This may indicate a carpet interaction model of the peptide with micelles. The molecular simulation study of peptide showed that the peptide consists of a well‐folded alpha‐helix core and unfolded extremities, which are responsible for the nature of the peptide interaction. The biophysical analyses can improve the atomic understanding of the mode of action of the peptide and help in future improvements of the peptide for clinical usage. Abstract :